Dateable swiping right, hooking up, and settling down while chronically ill and disabled - Slice, Jessica; Cupp, Caroline (Hachette Go, 2024)
"Disabled people date, have casual sex, marry, and parent. Yet, our romantic lives of are conspicuously absent from the media and cultural conversation. Sexual education does not typically address the specific information needed by disabled teens. Mainstream dating apps fail to include disability as an aspect of one's identity alongside race, ethnicity, gender identity, and sexual orientation. The few underutilized disability-focused apps are paternalistic and unappealing. Bestselling dating books do not address disability, and the few relationship books marketed to disabled people focus on the mechanics of sex rather than the complex interactions that create the conditions for it. In Dateable, disabled author and essayist Jessica Slice and disabled bioethicist and progressive faith leader Caroline Cupp team up to address the serious gap in the dating space. A dating guide made especially for disabled and chronically ill people, that calls in able bodied readers, Dateable is the first book on disabled dating and relationships. Slice and Cupp take on everything from Rom Com representation to dating apps to sex and breakups with a strong narrative underpinning and practical advice. The book is as much a practical tool as it is an empowering guide"--
Keywords: Behinderter Mensch; Rendezvous; People with disabilities / Social life and customs; Chronically ill / Social life and customs; Dating (Social customs); Sex; Personnes handicapées / Murs et coutumes; Amours; Sexualité; courtships; sexuality